511 INCREMENTAL VALUE OF RIGHT ATRIAL STRAIN ANALYSIS TO PREDICT ATRIAL FIBRILLATION RECURRENCE AFTER CARDIOVERSION. (15th December 2022) - Tomaselli, Michele; Cannone, Vincenzo; Muraru, Denisa; Oliverio, Giorgio; Gavazzoni, Mara; Heilbron, Francesca; Radu, Noela; Perelli, Francesco; Stucchi, Davide; Pece, Cinzia; Camponetti, Virginia; Rizzo, Salvatore; et al.
Abstract: Background: In patients with paroxysmal atrial fibrillation (AF), left atrial (LA) mechanics has been reported to be important to predict recurrences after cardioversion. However, the potential additive role of right atrial (RA) function in this setting remains to be tested. Accordingly, the aims of our study was to assess the added role of right atrial reservoir longitudinal strain (RARS) for prediction of AF recurrence after electrical cardioversion. Methods: we prospectively studied 130 (mean age 69±14, 55% men) consecutive patients with persistent AF who underwent electrical cardioversion, acquired between June 2020 and December 2021. Exclusion criteria were: presence of pacemaker, more than moderate mitral and tricuspid regurgitation, left or right ventricular dysfunction, prior cardiac surgery, and, inadequate acoustic window. LA and RA 2D-speckle-tracking echocardiography analyses were obtained from dedicated, non-foreshortened 4-ch and RV-focused apical 4-ch views respectively, using a dedicated software package (AFI LA, EchoPAC 204, GE Vingmed, Horten, Norway). The primary endpoint was AF recurrence. Results: after a follow-up period of 12 months, 60 patients (45%) reached the primary endpoint. The mean left ventricular ejection fraction (LVEF) was 56.5±8%, for all patients. No significant difference in LA (98±31 vs 94±30 mL, p= 0.333) and RA (68±26 vs 65±26 mL, p=0.286) volumes was detected between patients with and without AF recurrence, while left atrial reservoir strain (LARS, 10±6 vs 14±7%, p<0.001) and RA reservoir strain (RARS, 14±10 vs 16±8%, p<0.001) were significantly lower in patients with recurrent AF. Receiving operator characteristics curve analysis showed that the predictive power of LARS (AUC 0.68 [IC 95% 0.58-0.78]), was lower than RARS (AUC 0.75 [IC 95% 0.66-0.84]) (p<0.001, for all), with cut-off of 10.5% (sensitivity 62%, specificity 70%) and, 15.5% (sensitivity 75%, specificity 75%), respectively. Kaplan-Meier curve for time to primary endpoint showed that patients with LARS≤10.5% and RARS ≤15.5% had a significant risk for AF recurrences (log rank, p<0.001), even after correcting for confounding variables. However, at multivariable Cox regression RARS (HR 3.42 [CI 95% 1.72-6.8], p< 0.001) was the only parameter independently associated with the primary endpoint. Conclusions: RARS is an independent predictor of the recurrences of AF after electrical cardioversion and provides an incremental prognostic value over LARS. This study highlights the pivotal role of the assessment of bi-atrial remodeling in patients with AF.